Do voiding urodynamic parameters predict the success of adjustable transobturator male system (ATOMS) to treat postprostatectomy urinary incontinence?. Issue 6 (4th June 2020) - Virseda‐Chamorro, Miguel; Ruiz, Sonia; García, Gonzalo; Queissert, Fabian; Salinas, Jesús; Arance, Ignacio; Angulo, Javier C.
Abstract: Objective: To evaluate whether urodynamic voiding risk factors can be predictive of failure of postprostatectomy urinary incontinence (PPI) treatment with adjustable transobturator male system (ATOMS). Materials and Methods: We carried out a longitudinal study on 77 males treated for PPI with ATOMS. Patients were submitted preoperatively to a urodynamic study. The postoperative outcome was checked by pad‐test. Treatment success was defined as daily pad‐test below 10 mL. Statistical analysis used were Fisher exact test, χ 2 lineal by lineal test, Student t test, and logistic regression analysis. The signification level was set at 95% bilateral. Results: Treatment was successful in 54 patients (70%) achieving continence. The urodynamic parameters that related to postoperative continence outcome were the cystometric bladder capacity (direct relationship with continence ( P = .019), type of voiding (more probability to achieve continence in patients who voided voluntarily followed by patients with involuntary voiding and abdominal straining voiding) ( P = .034), Bladder Outlet Obstruction Index (BOOI) (inversely related with continence) ( P = .025), and maximum voiding abdominal pressure (inversely related with continence) ( P = .049). Multivariate analysis showed that cystometric bladder capacity (odds ratio [OR], 1.01; confidence interval [CI], 1.02‐1.00), BOOI (OR, 0.97; CI, 0.99‐0.94), and maximum abdominal bladder pressure (OR, 0.97; CI, 0.98‐0.94) were independent risk factors to predict treatment success after ATOMS implant. Conclusions: The study of functional voiding parameters is useful to know the risk factors that influence postoperative outcome of PPI with ATOMS device. These findings could be of primary importance to facilitate optimum patient selection for this implant and therefore improve operative results.